Broadband energy harvesting using acoustic black hole structural tailoring - Zhao, Liuxian; Conlon, Stephen C; Semperlotti, Fabio (Smart materials and structures, 2014)
This paper explores the concept of an acoustic black hole (ABH) as a main design framework for performing dynamic structural tailoring of mechanical systems for vibration energy harvesting applications. The ABH is an integral feature embedded in the host structure that allows for a smooth reduction of the phase velocity, theoretically approaching zero, while minimizing the reflected energy. This mechanism results in structural areas with high energy density that can be effectively exploited to develop enhanced vibration-based energy harvesting. Fully coupled electro-mechanical models of an ABH tapered structure with surface mounted piezo-transducers are developed to numerically simulate the response of the system to both steady state and transient excitations. The design performances are numerically evaluated using structural intensity data as well as the instantaneous voltage power and energy output produced by the piezo-transducer network. Results show that the dynamically tailored structural design enables a drastic increase in the harvested energy as compared to traditional structures, both under steady state and transient excitation conditions.